Retrospective review of neurodevelopmental outcomes in infants treated for neonatal abstinence syndrome. (May 2018) - Merhar, Stephanie; McAllister, Jennifer; Wedig-Stevie, Kathryn; Klein, Amy; Meinzen-Derr, Jareen; Poindexter, Brenda
Abstract Objective: Little is known about developmental outcomes in neonatal abstinence syndrome (NAS). We hypothesized that children treated for NAS would score lower than the normative sample on the Bayley Scales of Infant Development, 3rd edition. Study design: We performed a retrospective cohort study of 87 infants treated for NAS and evaluated at 2 years of age. Results: Children treated for NAS scored significantly lower than the norm (mean 100) on all 3 subscales (cognitive mean 96.5, language mean 93.8, motor mean 94.0, allp < 0.03). Children who lived with foster/adoptive families at follow up had higher cognitive scores (median 100 vs. 95, p = 0.03) than those who lived with biological relatives, and were less likely to have motor scores <85 (p = 0.02). Eight percent of children required treatment for strabismus. Conclusions: Children treated for NAS are at risk for lower developmental scores and higher rates of strabismus at age 2 than the general population.